POST PANDEMIC INNOVATION; A COLLABORATION AND ORGANIZATIONAL PERFORMANCE APPROACH - Mustainah Mappatoba; Suasa; Muhammad Ahsan Samad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to assess the performance of government organizations during the pandemic in the city of Palu, Indonesia. The current unprecedented pandemic crisis has pushed many organizations in an urgent state to innovate, including innovation in the performance of government apparatus in Indonesia. This study adopts the collaboration model developed by Shou et al., 2017 used to measure organizational collaboration consisting of 4 items, while the development model from Lee and Song, 2015 is used to measure organizational innovation consisting of 5 items, and Organizational performance developed by Tseng and Liao, 2015 is used to measure the performance of an organization consisting of 5 items. This research will focus on testing theoretical models that state that there is a collaborative relationship to organizational performance after Covid-19 in the city of Palu. Researchers test theoretical models to understand the consistency of theories so that they can be used as new scientific findings. This study uses quantitative research techniques with regression analysis techniques. The results of the study reveal the gap between the planned and implemented outcomes, this study also shows what service aspects of the community's view are effective in servants so that it will help identify and improve potential problems. This is critical for improving organizational performance in crisis sectors such as the handling of the Covid-19 pandemic in developing countries in particular Palu City, given the challenges associated with care systems and handlers in prevention in public health.